Critical analysis of radical scavenging properties of atorvastatin in methanol recently estimated via density functional theory - Bâldea, Ioan (Computational and theoretical chemistry, 2022)
In this communication we draw attention on serious flaws that plague recently reported antioxidant properties of atorvastatin (ATV) in methanol. First and foremost, we emphasize that the O-H bond dissociation energies (BDE) of about 400kcal/mol previously reported are completely wrong. Further, we present results refuting the previous claim that the proton affinity (PA) of ATV is smaller than that of the ascorbic acid. That unfounded claim relies on incorrect data for PA’s ascorbic acid (which we correct here) circulated in the literature. Further, we correct the values of the chemical reactivity indices (e.g., chemical hardness, electrophilicity index, electroaccepting and electrodonating powers), which were inadequately estimated previously via Kohn-Sham HOMO and LUMO energies. Finally, our updated values for O-H bond dissociation enthalpy (BDE = 91.4kcal/mol) and electron transfer enthalpy (ETE = 105.7kcal/mol) tentatively suggest that direct H-atom transfer (HAT) and sequential proton loss electron transfer (SPLET) may coexist.